Fig. 4 in Revision of Sthenelais Kinberg, 1856, Fimbriosthenelais Pettibone, 1971 and Eusthenelais McIntosh, 1876 (Polychaeta, Sigalionidae) in the Northeast Atlantic - Barnich, Ruth; Haaren, Ton Van (Zenodo, 2021)
Fig. 4. Sthenelais boa (Johnston, 1833). TUM 39683 (A–B, D–E) and SMF 10629 (C, F–I). A. Anterior end. B. Left elytron of segment 21. C. Detail of outer lateral elytral margin. D. Left parapodium of segment 21, anterior view. E. Same, posterior view. F. Capillary notochaeta, with details of simple or bidentate tip (not to scale). G–I.Neurochaetae of segment 19, all distal part. G. Upper simple, spinous neurochaeta. H. Upper slender compound falciger. I. Middle stout compound falciger. Scale bars: A–B = 1 mm; D–E = 250 µm; C, F–I = 100 µm. Published as part of Barnich, Ruth & Haaren, Ton Van, 2021, Revision of Sthenelais Kinberg, 1856, Fimbriosthenelais Pettibone, 1971 and Eusthenelais McIntosh, 1876 (Polychaeta, Sigalionidae) in the Northeast Atlantic, pp. 138-171 in European Journal of Taxonomy 740 on page 152, DOI:10.5852/ejt.2021.740.1287, http://zenodo.org/record/4649646